2007
DOI: 10.1007/s00270-007-9131-5
|View full text |Cite
|
Sign up to set email alerts
|

Shock Index Correlates with Extravasation on Angiographs of Gastrointestinal Hemorrhage: A Logistics Regression Analysis

Abstract: We applied multivariate analysis to the clinical findings in patients with acute gastrointestinal (GI) hemorrhage and compared the relationship between these findings and angiographic evidence of extravasation. Our study population consisted of 46 patients with acute GI bleeding. They were divided into two groups. In group 1 we retrospectively analyzed 41 angiograms obtained in 29 patients (age range, 25-91 years; average, 71 years). Their clinical findings including the shock index (SI), diastolic blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…In its evolution, an SI > 0.9 was proposed as an indicator of impending hemorrhagic shock (58,60,61). Indeed, there is compelling evidence suggesting that SI is more sensitive than either HR or SBP alone as an early predictor of hemorrhage (60,62,63), massive transfusion (64), morbidity (58), and mortality in geriatric patients (59,61). Based on the SI threshold of 0.9, doctrine would indicate that Group 2 would be considered at higher risk for developing shock than Group 1.…”
Section: A Model With a Reproducible Clinical Outcomementioning
confidence: 98%
“…In its evolution, an SI > 0.9 was proposed as an indicator of impending hemorrhagic shock (58,60,61). Indeed, there is compelling evidence suggesting that SI is more sensitive than either HR or SBP alone as an early predictor of hemorrhage (60,62,63), massive transfusion (64), morbidity (58), and mortality in geriatric patients (59,61). Based on the SI threshold of 0.9, doctrine would indicate that Group 2 would be considered at higher risk for developing shock than Group 1.…”
Section: A Model With a Reproducible Clinical Outcomementioning
confidence: 98%
“…There are few data describing the use of the shock index in LGIB, although the recent NCEPOD report that included LGIB, found that increasing shock index was associated with mortality 5. A shock index of ≥1 can also be used to predict extravasation of contrast on angiography in LGIB21 and therefore may be used to identify patients with active bleeding, who are likely to benefit from CTA. As the shock index reflects simply haemodynamic instability and is easy to calculate, its use is warranted even though there are few studies describing its use in LGIB.…”
Section: Management Algorithmmentioning
confidence: 99%
“…26% (152/587) had a shock index of >1 suggesting deficiencies in the clinical recognition of haemodynamic compromise. A shock index of one or greater has been shown to be predictive of active bleeding at imaging [9]. …”
Section: Methodsmentioning
confidence: 99%